2020
DOI: 10.3390/cancers12092454
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sequencing Analysis Identified a Specific Subset of Mutations Distinctive of Biphasic Malignant Pleural Mesothelioma

Abstract: Malignant Pleural Mesothelioma (MPM) is a heterogeneous disease. Morphologically, three different phenotypes are distinguishable: epithelioid (e-), sarcomatoid (s-) and biphasic (biph-) MPM, the latest, being a mixture of e- and s-MPM cells. Being an intermediate entity, management of biph-MPM, remains debatable and controversial, with different guidelines recommending distinct approaches. Identification of biph-MPM associated genetic alterations, through deep sequencing analysis, may provide useful tools to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In Torricelli et al. RDX and MXRA5 are present in 42% and 40.6% of the cohort, respectively and authors stated that MXRA5 is specific for the biphasic histotype together with NOD2 ( 143 ). The same genes were also described in the RAMES study where RDX and MXRA5 represented the 42% and 23% of MPMs, respectively, however in this case MXRA5 was identified in both epithelioid and non-epithelioid histotypes ( 144 ).…”
Section: Therapeutic Implications Of Genomics and Transcriptomics Evidencesmentioning
confidence: 95%
See 1 more Smart Citation
“…In Torricelli et al. RDX and MXRA5 are present in 42% and 40.6% of the cohort, respectively and authors stated that MXRA5 is specific for the biphasic histotype together with NOD2 ( 143 ). The same genes were also described in the RAMES study where RDX and MXRA5 represented the 42% and 23% of MPMs, respectively, however in this case MXRA5 was identified in both epithelioid and non-epithelioid histotypes ( 144 ).…”
Section: Therapeutic Implications Of Genomics and Transcriptomics Evidencesmentioning
confidence: 95%
“…Interestingly, the same work reported gene fusions such as EWSR1-ATF1 and FUS-ATF1 and ALK rearrangements that are hardly found in pleural mesothelioma and seem to be specific for young women as compared to ALK-wild type patients but might respond to targeted treatment (127,141,142) (Table 2). Two recent studies have reported novel somatic mutations in RDX and MXRA5 genes, independently (143,144). In Torricelli et al RDX and MXRA5 are present in 42% and 40.6% of the cohort, respectively and authors stated that MXRA5 is specific for the biphasic histotype together with NOD2 (143).…”
Section: Therapeutic Implications Of Genomics and Transcriptomics Evidencesmentioning
confidence: 99%
“…H3K9 trimethylation possesses the ability to form heterochromatin, which silences gene transcription and remodels the chromatin structure [ 1 , 9 , 10 ]. Overexpression and downregulation of SETDB1 have been widely found in various cancers, but the detailed mechanisms are still unclear [ 2 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Here, we summarize the biological functions of SETDB1 and its therapeutic relevance in lung cancer and mesothelioma, describing possible diagnostic and therapeutic prospects.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological grading also offers the best measure of risk stratification of these tumors, being that sarcomatoid the most aggressive and deadly form of MPM. Even if some attempts have been performed [52,53], genetic alterations seem not to account for this diversity. By contrast, hierarchical clustering on the basis of deep gene expression profiling always recapitulates these three categories, with biphasic MPM always in a wide and largely heterogeneous spectrum in between the other two histotypes.…”
Section: Morphological Differentiation In Mpm Is a Matter Of Altered Gene Expressionmentioning
confidence: 99%